Hiv-Exposed but Uninfected Infants: Identifying Developmental Delay and the challenges faced in Accessing Developmental Services from a Canadian Tertiary Centre. (1st June 2016) - Abdulwahab, K; Olson, L; Adjudani, A; Pakzad, Z; Alimenti, A; Sauvé, L
Abstract: BACKGROUND: Children born to HIV-positive mothers but are HIV uninfected (HEU) are at increased risk for adverse developmental outcomes. The literature suggests that the increased risk is more related to social determinants of health rather than effects of perinatal exposures to HIV and antiretrovirals. Developmental screening and early referral do result in improved outcomes and so HEUs should benefit from anticipatory guidance and early specialist referral. OBJECTIVES: We aimed to identify the rate of development screening, identification and referral of developmental concern, and referral completion in a provincial family-centered HIV clinic caring for 20-30 HIV exposed newborns per year and secondarily identify barriers to referral completion. DESIGN/METHODS: We conducted a retrospective review of all of the HEU cared for at this outpatient clinic born between January 1, 2008 and June 30, 2013 to examine the frequency of developmental concerns, referral rates for children with documented concerns, and referral outcomes. RESULTS: We reviewed 112 subjects: 64 (57%) male; 87 (77%) born at term (>37 weeks). 78 (66%) of the families had one or more social vulnerabilities (parental ill health apart from HIV, poverty, limited literacy, limited English language skills, etc), including 43 (38%) who had some involvement with child protection services. 104 (92.8%) had at least one documented developmental assessment using standardized tools. Among these 104, 46 (44.2%) were noted to have a developmental concern and of those, 40 (87.0%) were referred to at least one developmental service provider or general pediatrician. There were a total of 43 referrals to developmental service providers; 58.1% occurred at time of study completion, and 60.0% for which recommendations were formally communicated. Of 36 referrals to general pediatricians, 69.4% had occurred, 92.0% of which recommendations communicated back to the clinic. Barriers to referral completion included inability to contact caregivers (7.3%), patient no-show (13.0%), waiting lists (23.2%), and other (56.5%). CONCLUSION: The large majority of patients were screened and referred when indicated, but a significant number of patients either were not assessed by the secondary provider, or no information was communicated back to the clinic. Multiple barriers at the clinic, patient, and referral centre level were identified. The discrepancy in referral completion between developmental service provider referrals and general pediatrician referrals, may further highlight the difficulty HEU families have navigating our provincial developmental services. Future work will examine how to overcome these barriers in a vulnerable population.